Advanced Intelligent Systems for Sustainable Development (AI2SD'2018) Volume 5: Advanced Intelligent Systems for Computing Sciences - Ezziyyani, Mostafa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes the outcomes of the International Conference on Advanced Intelligent Systems for Sustainable Development (AI2SD-2018), held in Tangier, Morocco on July 12-14, 2018. Presenting the latest research in the field of computing sciences and information technology, it discusses new challenges and provides valuable insights into the field, the goal being to stimulate debate, and to promote closer interaction and interdisciplinary collaboration between researchers and practitioners. Though chiefly intended for researchers and practitioners in advanced information technology management and networking, the book will also be of interest to those engaged in emerging fields such as data science and analytics, big data, internet of things, smart networked systems, artificial intelligence, expert systems and cloud computing. .
Intelligent reservation systems based on MAS & data mining method -- A Lightweight Ciphertext-Policy Attribute-Based Encryption for Fine-Grained Access Control -- Generate a Meta-Model Content for Communication Space of Learning Management System Compatible with IMS-LD -- Designing an IMS-LD Model for Communication Space of Learning Management System -- A smart cascaded H-bridge multilevel inverter with An optimized modulation techniques increasing the quality and reducing harmonics -- Approaches and algorithms for resource management in OFDMA access mode: Application to mobile networks of new generation -- A new efficient technique to enhance quality of service in OLSR protocol -- Performance Assessment of AODV, DSR and DSDV in an Urban VANET Scenario -- Exploiting NoSQL Document Oriented Data Using Semantic Web Tools -- Analytical study of the performance of communication systems in the presence of fading -- Android Applications analysis results using PerUpSecure Tool -- Novel configuration of Radio over Fiber system using a hybrid SAC-OCDMA/OFDM technique -- A Hybrid Multilingual Sentiment Classification using Fuzzy Logic and Semantic Similarity -- Fuzzy semantic-based similarity and big data for detecting multilingual plagiarism in Arabic documents -- Contribution to the improvement of the Quality of Service over Vehicular ad-hoc Network -- Sustainable Development: Clustering Moroccan Population Based on ICT and Education -- Datamining for Fraud Detecting, State of the art -- Elephant Herding Optimization Algorithm for the travelling salesman problem -- Deep learning technology for identifying a person of interest in real-world -- The Discrete swallow swarm optimization for flowshop scheduling problem.
Keywords: Computational intelligence; Artificial intelligence; Medical informatics; Computational Intelligence; Artificial Intelligence; Health Informatics